Progression of Focal to Diffuse Thyroid Uptake Detected by 18F-FDG PET/CT: Malignant Metastatic Disease or Benign Thyroiditis?. (September 2018) - Thuillier, Philippe; Crouzeix, Geneviève; Descourt, Renaud; Salaun, Pierre-Yves; Abgral, Ronan
Abstract : Abstract: A 49-year-old man was referred to our department for an assessment of a cerebral metastasis of unknown primary with 18 F-FDG PET/CT. This imaging led to detection of a suspected pulmonary primary carcinoma, as well as an incidental left focal thyroid uptake. An ultrasonography, performed a month later, revealed a thyroiditis aspect. An anti-PD1 immunotherapy was also proposed 2 months later after confirmation of a lung adenocarcinoma. A second baseline FDG PET/CT surprisingly showed a diffuse thyroid uptake. A fine-needle aspiration biopsy of thyroid parenchyma finally revealed a diffuse involvement from lung adenocarcinoma (ie, primary lung metastasis to the thyroid gland).